Perencanaan Strategi Sistem Informasi Dengan Metode WARD And PEPPARD pada SMP Islam Sudirman Ambarawa - Kurniawan, Restu Yoga; Fibriani, Charitas (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Sudirman Islamic Junior High School has introduced information systems in its operations, the problem arises because the implementation has not reached its maximum potential. One of the main obstacles is the lack of integration between the various components of the information system resulting in poor integration, and less efficient business processes in the school. The impacts include redundancies in data collection and processing, difficulties in accessing necessary information, and delays in decision-making. All of these threaten the ability of Sudirman Islamic Junior High School to maintain and improve their competitiveness in the world of education. In planning the information system strategy at Sudirman Islamic Junior High School, the Ward and Peppard framework approach was used using various analysis tools. Value Chain is used to evaluate the internal and external aspects of the business environment. SWOT is used to analyze internal and external factors that affect the information system. Furthermore, there are recommendations for information system applications such as E-Learning, Siakhlak, Sikelulusan, and SiPerpus that will help improve the effectiveness and efficiency of school operations. These applications then become guidelines in decision-making regarding implementation. All these recommendations and mapping will be the main guide in directing the development of information systems at Sudirman Islamic Junior High School in the future.